The Dialectic of Faith and Plurality: Assessing the Relevance of Al-Hallaj’s Sufi Thought in the Contemporary Era - Vici Ramananda; Gazali Gazali (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study analyzes al-Hallaj’s Sufi thought within the dialectical framework of particular faith and universal plurality, while formulating its relevance to contemporary religious life in Indonesia. The research is motivated by Indonesia’s pluralistic society, which remains vulnerable to identity-based conflicts, highlighting the need for a theological and spiritual foundation to address intolerance and religious exclusivism. This study employs a qualitative descriptive method with a library research approach. A hermeneutic-philosophical analysis is applied to the primary sources, namely Kitab al-Tawasin and Diwan al-Hallaj, supported by Louis Massignon’s authoritative scholarship and triangulated with relevant peer-reviewed journal articles. The findings reveal three major points. First, authentic faith in al-Hallaj’s Sufism is understood as an inner spiritual experience awakened through divine love (mahabbah) and culminating in fanā’, as symbolized by the expression Ana al-Haqq. Second, the concept of Wahdat al-Adyan, grounded in the doctrine of Nur Muhammad, asserts that religious differences represent historical and exoteric diversity, whereas their essential orientation remains the worship of the One God. Third, al-Hallaj’s thought provides a spiritual foundation for strengthening religious moderation in Indonesia by enriching the meaning of Bhinneka Tunggal Ika while offering an ethical and theological response to radicalism, intolerance, and identity politics. This study contributes a theoretical synthesis linking classical Sufi spirituality with inclusive social ethics in contemporary plural societies.